Psychological Care Of Attention Disorder In The Light Of Neuropsychological Studies (El-Wahat Journal for Research and Studies, 2023)
Abstract: This study aims to address the issue of attention and learning disorders and explain it in the light of neuropsychological studies, by defining the concept of this disorder, its causes, and types, as well as the disclosure of diagnostic criteria and the most important medical, psychological and educational treatments.Keywords: Attention Deficit Disorder - Diagnosis - Treatment - Neuropsychological studies.